2011
DOI: 10.1371/journal.pone.0028759
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trials of HIV/AIDS Prevention and Treatment in Africa: Results from the Cochrane HIV/AIDS Specialized Register

Abstract: IntroductionTo effectively address HIV/AIDS in Africa, evidence on preventing new infections and providing effective treatment is needed. Ideally, decisions on which interventions are effective should be based on evidence from randomized controlled trials (RCTs). Our previous research described African RCTs of HIV/AIDS reported between 1987 and 2003. This study updates that analysis with RCTs published between 2004 and 2008.ObjectivesTo describe RCTs of HIV/AIDS conducted in Africa and reported between 2004 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Few studies were funded by African organizations, and specifically, African governments. This is similar to other previous studies which also observed few funders from the continent 23,24 . Overall, the lack of funding from African governments may reflect lack of economic ability, political will or capacity to fund research.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies were funded by African organizations, and specifically, African governments. This is similar to other previous studies which also observed few funders from the continent 23,24 . Overall, the lack of funding from African governments may reflect lack of economic ability, political will or capacity to fund research.…”
Section: Discussionsupporting
confidence: 93%
“…(11) Smith et al examined research partnerships between LMIC and other country researchers and made some recommendations, most importantly emphasizing the importance of empirical research into capacity building in LMICs. (10,12) In this context, the aim of this study was to examine trends in first-authorship by researchers from LMIC institutions over time (LMIC first-authors hereafter). If capacity building initiatives in recent years have been successful, then the number and proportion of articles with first-authors from LMIC institutions would be expected to have increased.…”
Section: Introductionmentioning
confidence: 99%
“…This is linked to the large number of multi-center trials with sites in the Africa region that are collaborating to answer questions for this region. This is encouraging as previous studies of published trials noted that not many trials were being conducted in Africa (Siegfried et al, 2005;Zani et al, 2011). The increase in the number of African principal investigators is equally encouraging as it is an indicator of regional capacity to conduct research.…”
Section: Trial Locations and Fundingmentioning
confidence: 69%